2012
DOI: 10.1002/etc.1775
|View full text |Cite
|
Sign up to set email alerts
|

Development of a highly sensitive assay for enzyme-mediated reductive degradation of polychlorinated dibenzo-p-dioxin

Abstract: The degradation of 2-chloro-4,5-O-(4'-methyl-7', 8'-diphenyl)ether (CMDPE), an analog of 2,7-dichlorodibenzo-p-dioxin (2,7-DCDD), mediated by Geobacillus sp. UZO 3 cell-free extract was monitored. Ethyl acetate extracts of a complete reaction mixture incubated at 65°C for 18 h were analyzed either by thin layer chromatography (TLC) fractionation coupled with spectrometric detection or by gas chromatography-mass spectrometry (GC-MS). The reaction product 4-methylumbelliferone (4MU) was successfully isolated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the present study, we developed a new on‐line assay of G6PDH enzyme based on TLC. As one of the oldest chromatographic methods, TLC has been applied for analysis of enzyme reactions in a few off‐line (or off‐plate) studies recently, in which enzyme reactions are carried out in a sample vial and TLC technique is used only for separation and detection of the products and unreacted substrates . Alternatively, several interesting studies have reported qualitative on‐plate inhibition assays based on TLC technique .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we developed a new on‐line assay of G6PDH enzyme based on TLC. As one of the oldest chromatographic methods, TLC has been applied for analysis of enzyme reactions in a few off‐line (or off‐plate) studies recently, in which enzyme reactions are carried out in a sample vial and TLC technique is used only for separation and detection of the products and unreacted substrates . Alternatively, several interesting studies have reported qualitative on‐plate inhibition assays based on TLC technique .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Because of its widespread use, it is necessary to have an indepth study of its properties and develop appropriate methods for determining hymecromone. There have been some methods reported for the determination of hymecromone, such as high-performance liquid chromatography, 7 GC-MS 8 and electrochemical methods. [9][10][11] Comparing among these reported literature studies, electrochemical methods have some advantages in the determination of hymecromone, such as high sensitivity, easy operation, low cost and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Transformants in the gene library of G. thermodenitrificans UZO 3 were screened for degradation activity using 2,7,-dichlorodibenzo-pdioxin (2,7-DCDD) as substrate. The enzymatic activity was evaluated by the detection of 4',5-dichloro-2hydroxydiphenyl ether (DCDE), a degradation intermediate (Suzuki et al, 2011(Suzuki et al, , 2012. As a result, we have cloned the gene for dioxin reductive ethrase dreE.…”
Section: Cloning and Sequence Of The Gene For Dioxin Reductive Ethera...mentioning
confidence: 99%